2014
DOI: 10.1017/s0001924000009209
|View full text |Cite
|
Sign up to set email alerts
|

Transonic aerofoils admitting anomalous behaviour of lift coefficient

Abstract: Transonic flow past a Boeing 737 Outboard aerofoil and Whitcomb one with a deflected aileron is studied. The flow simulation is based on the system of Reynolds-averaged Navier-Stokes equations. The numerical study demonstrates the existence of free-stream conditions in which small perturbations produce abrupt changes of the lift coefficient. Also the simulation reveals adverse conditions in which aileron deflections have no influence on the lift.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…1 [6,8]. Also the instability of closely spaced supersonic regions was examine Whitcomb airfoil with a deflected aileron at the Reynolds number Re=5.610 6 [9].…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…1 [6,8]. Also the instability of closely spaced supersonic regions was examine Whitcomb airfoil with a deflected aileron at the Reynolds number Re=5.610 6 [9].…”
Section: Problem Formulationmentioning
confidence: 99%
“…This phenomenon was scrutinized for a number of sym profiles [6][7], as well as for the asymmetric J-78 airfoil whose upper surface is nearly fla midchord region [6,8]. Also the instability of closely spaced supersonic regions was examin Whitcomb airfoil with a deflected aileron at the Reynolds number Re=5.610 6 [9].…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent numerical studies of inviscid and turbulent flow confirmed the abrupt restructuring of 2D flow field due to the coalescence of S-regions at increasing ∞ or their rupture at decreasing ∞ . This phenomenon was scrutinized for a number of symmetric airfoils [10,11] and also for symmetric ones, such as the J-78 airfoil, the Boeing 737 midspan profile [12], and a Whitcomb airfoil with aileron deployments [13]. It was shown that both flow regimes (with the double and merged S-regions) can be either steady or exhibit self-exciting oscillations near the trailing edge due to the instability of the separated boundary layer.…”
Section: Introductionmentioning
confidence: 99%